Science with the Murchison Widefield Array: Phase I results and Phase II opportunities. (2019) - Beardsley, A. P.; Johnston-Hollitt, M.; Trott, C. M.; Pober, J. C.; Morgan, J.; Oberoi, D.; Kaplan, D. L.; Lynch, C. R.; Anderson, G. E.; McCauley, P. I.; Croft, S.; James, C. W.; et al.
Abstract: The Murchison Widefield Array (MWA) is an open access telescope dedicated to studying the low-frequency (80–300 MHz) southern sky. Since beginning operations in mid-2013, the MWA has opened a new observational window in the southern hemisphere enabling many science areas. The driving science objectives of the original design were to observe 21 cm radiation from the Epoch of Reionisation (EoR), explore the radio time domain, perform Galactic and extragalactic surveys, and monitor solar, heliospheric, and ionospheric phenomena. All together $60+$ programs recorded 20 000 h producing 146 papers to date. In 2016, the telescope underwent a major upgrade resulting in alternating compact and extended configurations. Other upgrades, including digital back-ends and a rapid-response triggering system, have been developed since the original array was commissioned. In this paper, we review the major results from the prior operation of the MWA and then discuss the new science paths enabled by the improved capabilities. We group these science opportunities by the four original science themes but also include ideas for directions outside these categories.